The role of word-of-mouth and celebrity endorsement in online consumer-brand relationship: the context of Instagram - Loureiro, S. M. C.; Sarmento, E. M. (2018 Global Fashion Management Conference, 2018)
The aims of this study are to understand the influence of celebrity endorsement on consumers’ word-of-mouth and decision behavior, that is: (i) understand the influence of the number of followers of the celebrity and the positive/negative valence of the messages conveyed by them in the intention to buy and their intention to generate eWoM; (ii) analyzing how the behavior of a celebrity (antisocial vs. pro-social) may affect the perception of its credibility, the intention of the consumers to relate to the celebrity in the social networks and the social identification with it; (iii) understand the impact of celebrity messages on brands and products present in social networks. To achieve this goal a quantitative methodology for the development of research was adopted, selecting the application of a survey as the information collection instrument. The sample is selected by convenience sampling method, collecting 241 responses, 122 females and 119 males. Findings show: (i) concerning the intention to purchase, female seem to be more influenced by the opinions and recommendations of celebrities, while male tend to be more likely to generate e-word-of-mouth into their contact network through social media. (ii) Regarding to antisocial versus prosocial type of celebrity, celebrities with a prosocial behavior seems to have a greater influence for both genders in the way they identify with celebrity and their willingness to relate to them. (iii) Female tends to feel higher purchase intention when exposed to an endorsement, where celebrity promotes a brand or product through its Instagram account.